Modernist literature and postcolonial studies - Patke, Rajeev S. (Rajeev Shridhar) (Postcolonial literary studies., 2013)
Provides a fresh account of modernist writing in a perspective based on the reading strategies developed by postcolonial studies Neither modernity nor colonalism (and likewise, neither postmodernity nor postcoloniality) can be properly understood without recognition of their intertwined development. This book interprets modernity as an asymmetrically global phenomenon complexly connected to the course of Western imperialism, and demonstrates how the impact of Western modernism produced new developments in writing from all the former colonies of Europe and the US. These developments constitute the afterlife of Western modernism. The various ways in which the aesthetic ideologies and writing strategies of Western modernism have been adapted, transposed and modified by some of the most innovative writers of the twentieth century is demonstrated in the book through a set of case studies, each of which juxtaposes a canonical modernist text with a postcolonial text that shows how modernist modes metamorphosed in interaction with the turbulent and volatile realities of colonies and new nations struggling to arrive at a modernity of their own in contexts marked by colonial histories. Thus Kafka's allegories are juxtaposed with the use of allegory in writers like Salman Rushdie and J.M.Coetzee; the gendered modernity of Virginia Woolf is juxtaposed with the disturbing and powerful fictions of writers such as Jean Rhys and Katherine Mansfield; the intellectualized and urbanized spirituality of T.S. Eliot's The Waste Land is re-read in the revisionist contexts created by the brilliant and troubled urban spirituality of writers such as Arun Kolatkar from India and a text such as The Woman Who Had Two Navels, from the Philippines. Key Features:. A detailed timeline that chronicles significant events and publications concerning modernist and (post)colonial cultures A fresh account of modernity and modernism as global phenomena interconnected An overview of modernist ideology in a context alert to the interface between the aesthetic and the political Four case studies, which re-read canonical modernist texts or authors in a perspective informed by postcolonial studies A new interpretive account of the relation between 'postmodern' and 'postcolonial' An annotated reading list to guide further explorations in the fields of modernist and postcolonial culturesinterconnected